ONLINE ORDERING SYSTEM AND CONSUMER ACCEPTANCE FORFOOD ORDERING APP IN CHENNAI - Muthumani, Dr. S.; Kumar, M. Manoj (The journal of contemporary issues in business and government, 2023)
Online ordering of food in India is still in its early stages despite gaining visibility recently. “Despite the visible popularity of online food ordering,we reckon only 27 per cent of the 40 million online shoppers are ordering food online,’’ a report said. E- commerce companies in the food-tech space are present across the delivery value- chain in the form of order aggregators such as Swiggy, Zomato, Dunzo with outsourced delivery; as full-stack food delivery companies such as Freshmenu and Holachef; and as B2B delivery outfits such as Grab, Roadrunnr and Shadowfax, which work with aggregators and restaurants.This paper deals with evaluation of the competitor analysis towards different services offered by online food ordering companies and the effect on consumer online ordering this study has been conducted for online food ordering app among students and IT professionals. . The outcome of this research helps in understanding the services like discounting facilities, food delivery, information of restaurants, cost of food, review and ratings on hotels, proximity are few of the important factors considered in comparing the services of online food ordering companies with its competitor’s services that are crucial from the point of view of consumers.